Perbandingan Norma Pidana Pencemaran Nama Baik Online Dalam Hukum Indonesia Dan Singapura - Mutia Aulia Apriadi; Naurah Edsa Zakiyah; Nadine Alysa Azura; Dhiyaa Husniyyah; Fourega Gamelia Lubis; Asep Suherman (CV. ITTC INDONESIA, 2026)
The rapid expansion of digital technology in Southeast Asia has intensified online interactions while simultaneously increasing cases of online defamation. This development creates tension between the need to protect individual reputation and the guarantee of freedom of expression, particularly in light of differing regulatory approaches between Indonesia and Singapore. This study aims to analyze the criminal regulation of online defamation in both jurisdictions, identify their similarities and differences, and formulate recommendations for a more proportionate legal framework. The research employs normative legal research using statute, comparative, conceptual, and case approaches, analyzed qualitatively through grammatical, systematic, and teleological interpretation. The findings indicate that Indonesia still faces issues of normative ambiguity and relatively expansive criminalization, whereas Singapore adopts a more selective approach with civil remedies as the primary mechanism and criminal law positioned as ultimum remedium. These results highlight the need for normative reformulation, strengthened enforcement guidelines, and harmonization with international human rights standards. In conclusion, Indonesia’s cyber defamation regime should move toward a more proportionate, precise, and balanced model that protects reputation without undermining freedom of expression.